2014
DOI: 10.1186/s13075-014-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

Local intra-articular injection of rapamycin delays articular cartilage degeneration in a murine model of osteoarthritis

Abstract: IntroductionRecent studies have revealed that rapamycin activates autophagy in human chondrocytes preventing the development of osteoarthritis (OA) like changes in vitro, while the systemic injection of rapamycin reduces the severity of experimental osteoarthritis in a murine model of OA in vivo. Since the systemic use of rapamycin is associated with numerous side effects, the goal of the current study was to examine the beneficial effect of local intra-articular injection of rapamycin in a murine model of OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
165
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 42 publications
(44 reference statements)
5
165
4
Order By: Relevance
“…Genetic ablation of cartilage mTOR (47) or inhibition of mTOR with the drug rapamycin (48,49) reduces the expression of catabolic enzymes and maintains cartilage viability in experimental OA. Here we establish that mTORC1 is activated early (within 24 h) in chondrocytes following a mechanical injury.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic ablation of cartilage mTOR (47) or inhibition of mTOR with the drug rapamycin (48,49) reduces the expression of catabolic enzymes and maintains cartilage viability in experimental OA. Here we establish that mTORC1 is activated early (within 24 h) in chondrocytes following a mechanical injury.…”
Section: Discussionmentioning
confidence: 99%
“…Sirolimus inhibits the severity of cartilage degeneration and fibrosis in mouse models of OA and SSc, respec tively [152][153][154][155] ; however, the results of an early phase trial of sirolimus in patients with SSc showed adequate safety profiles, but were inconclusive 156 , and sirolimus is not currently being investigated for use in the treatment of OA or SSc. No published clinical trials have specifically addressed the safety of sirolimus in the treatment of OA, so further studies will be of great interest in determining whether sirolimus is capable of modulating pathologies associated with autophagy in this setting.…”
Section: Autophagy-modulating Therapiesmentioning
confidence: 92%
“…Based on current knowledge, autophagy, a self-protective mechanism in chondrocytes, has become a promising target to improve the viability and function of chondrocytes, thereby impeding the progress of OA [19, 20]. Autophagy may be activated in response to various stress stimuli, providing protective roles for chondrocytes [21].…”
Section: Discussionmentioning
confidence: 99%